Simulation of Flexible Link Aerator and Control with PID Using Ziegler Nichol’s Method - Mohammad Noor, Abdul Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The failure of keeping prawn alive in a pond has cause a lot of pawn farmer to take a loss which will cost a lot of money. By doing a research, its known that one of the reasons why the prawn is dying is because of the lack of oxygen in the pond. We know that water is made of combination between Oxygen and Hydrogen. So based on that we know that inside water exists Oxygen which is needed for the prawn to breath inside the water. By using this project in the prawn pond, the concentration of Oxygen inside the pond can be increased. By increasing the concentration of oxygen inside the pond. The death rate of the pawn inside the pond can be decreased. By using the PID controller with Ziegler Nichols method it can further decreased the death rate of prawn, and it increased the efficiency of the controller that used to controller the rate of concentrated oxygen inside the pond. The results show that the value that obtain before and after implementation of the Ziegler Nichols method is different and there is improvement in the value after the implementation of Ziegler Nichols method. The value of peak response is reduced to 1 from 1.28, while the value of overshoot is reduced to zero from 28.1 value that obtained. The time taken is reduce from 3 to 1.75. Settling time value decrease from 8.91 to 2. While the value that increasing the rise time where its increase from 1.19 to 1.5. final value for both is still same.